SMART EDUCATORS FOR DIGITAL AGE STUDENTS - Nurul Fauziyyah (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2020)
The purpose of this study was to review the shifting paradigm of educators that should be adjusted to the development and needs of the current generations or in other words educators must be smart to digital age students. This study was conducted by previous studies and associated with the facts that occur at this time or also known as a literature study. The data analysis method used in this study is descriptive analysis method. Results showed that the root reason to shift the old paradigm in education system is not just about technology, but it tends to the needs of ‘new environment’ in learning process for digital age students. Having good skill in technology is a must, but smart educators have greater challange to interprate that skill to create an interesting learning process to absorb the best result from the education system. That is why educators have to shift the old paradigm in education system. Educators have to improve their creativity to create an enjoyable class to attract students’ attention.